Ritual Hari Raya Agama: Histeria Konsumsi Massa dan Khotbah Industri Budaya - Lukmantoro, Triyono (Jurnal ILMU KOMUNIKASI, 2004)
The purposes of religion ritual are embodying conscience collective in society to gain sacred values. But, Ã‚Â ronically, in consumer society the religion ritual has been transformed to be means for excessive shopping on hysteria stage. More dramatically, television stations as motors of the culture industry to present religion spectacles use this momentum. It means that television pretends to celebrate the ritual, but in fact television only makes the largest profits.